MOTOR CHARACTERISTICS OF ELEMENTARY SCHOOL VOLLEYBALL PLAYERS IN BOA VISTA - RORAIMA. (Fiep Bulletin - online, 2024)
Introduction: Volleyball is a tool that works the variables of balance, speed, agility, and coordination, which implies motor and cognitive development. It is a social factor that stimulates and motivates, which helps in strengthening the body, because it explores various body movements. Objectives: The objective of this study was to evaluate the motor profile of schoolgirls practicing volleyball in Boa Vista/Roraima. Methods: Nine female primary schools’ students were analyzed. Methodology: The instrument used to measure the level of motor development was the MABC2 which characterizes the variables Manual Dexterity, Throwing and Receiving and Balance. Results: The results found show that the level for each motor skill had a result much lower than expected, in the skill of manual dexterity 8.34%, launch and receive 21.22% and balance 48.55% it was verified that the average percentile of the practitioners, already the general result showed that about 66% low of the average. Conclusion:  We conclude that school practitioners obtained a large deficit in motor development in this investigation.Keywords: Development Motor, Education Physical, Volleyball.